Economic geography aspects of the Panama Canal - Rauch, F; Maurer, S (University of Oxford, 2019)
This paper studies how the opening of the Panama Canal in 1914 changed market access and influenced the economic geography of the United States. We compute shipment distances with and without the canal from each US county to each other US county and to key international ports and compute the resulting change in market access. We relate this change to population changes in 20-year intervals from 1880 to 2000. We find that a 1 percent increase in market access led to a total increase of population by around 6 percent. We compute similar elasticities for wages, land values and immigration from out of state. When we decompose the effect by industry, we find that tradable (manufacturing) industries react faster than non-tradable (services), with a fairly similar aggregate effect.